2016
DOI: 10.1002/jssc.201600574
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of essential oils in Atractylodes lancea and Atractylodes koreana by gas chromatography with mass spectrometry

Abstract: Atractylodes rhizome is a valuable traditional Chinese medicinal herb that comprises complex several species whose essential oils are the primary pharmacologically active component. Essential oils of Atractylodes lancea and Atractylodes koreana were extracted by hydrodistillation, and the yield was determined. The average yield of essential oil obtained from A. lancea (2.91%) was higher than that from A. koreana (2.42%). The volatile components of the essential oils were then identified by a gas chromatography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 18 publications
2
14
0
Order By: Relevance
“…It is mainly distributed in Heilongjiang, Hebei, Jiangsu, Zhejiang, Anhui and Hubei province. It has been firstly reported in Shen Nong Ben Cao Jing, the earliest masterpiece about Chinese medicine [6], reputed to invigorate the spleen and eliminate dampness. And it is commonly used for the treatment of rheumatic diseases, influenza, digestive disorders and other diseases in clinical [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is mainly distributed in Heilongjiang, Hebei, Jiangsu, Zhejiang, Anhui and Hubei province. It has been firstly reported in Shen Nong Ben Cao Jing, the earliest masterpiece about Chinese medicine [6], reputed to invigorate the spleen and eliminate dampness. And it is commonly used for the treatment of rheumatic diseases, influenza, digestive disorders and other diseases in clinical [7].…”
Section: Introductionmentioning
confidence: 99%
“…Therefor many cultivated varieties were also used as Atractylodis rhizome in the market. There have been studies showed that there are obvious differences of volatile components and oxygenous sesquiterpenoid in A. lancea and cultivated varieties [3, 6].…”
Section: Introductionmentioning
confidence: 99%
“…DC., which belongs to the Asteraceae (Compositae) plant family, has been widely used as traditional medicine in many countries, including China and Japan. The main pharmacologically active components of A. lancea are present in the volatile oils and include atractylon, atractylodin, hinesol and β-eudesmol [ 1 , 2 ]. Previous pharmacological studies have demonstrated that the extract and chemical constituents of A. lancea have promising anti-inflammatory, anti-cancer, and anti-microbial effects and have been used as a remedy for gastritis and gastric ulcers [ 3–5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there are several easily confused species of the Atractylodes genus that have been used as the adulterants of 'Cangzhu' in the northeast China, such as Atractylodes koreana (Nakai) Kitam (Linrong 1987). However, the primary components obtained from A. lancea and A. koreana are significantly different, importantly the contents of atractylon and atractylodin (Liu et al 2016). In this study, we characterized the structure of the complete chloroplast (cp) genome of A. koreana and analyzed its phylogenetic relationship with other species in Atractylodes genus.…”
mentioning
confidence: 99%
“…However, the primary components obtained from A. lancea and A. koreana are significantly different, importantly the contents of atractylon and atractylodin (Liu et al. 2016 ). In this study, we characterized the structure of the complete chloroplast (cp) genome of A. koreana and analyzed its phylogenetic relationship with other species in Atractylodes genus.…”
mentioning
confidence: 99%